2015
DOI: 10.1021/acs.iecr.5b03135
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Uranium from Seawater: Promising AI Series Adsorbents

Abstract: A new series of adsorbents (AI10 through AI17) were successfully developed at ORNL by radiation induced graft polymerization (RIGP) of acrylonitrile (AN) and vinylphosphonic acid (VPA) (at different mole to mole ratios) onto high surface area polyethylene fiber, with high degrees of grafting (DOG) varying from 110 to 300%. The grafted nitrile groups were converted to amidoxime groups by reaction with 5 wt % hydroxylamine at 80 °C for 72 h. The amidoximated adsorbents were then conditioned with 0.44 M KOH at 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 37 publications
(51 reference statements)
1
109
0
Order By: Relevance
“…[3,[20][21][22][23][24][25] However, in this study, we found that 10 × 10 −3 m NaOH solution is enough to "active" the imide dioxime and/or amidoxime groups sufficiently. In most of the previous studies, 0.44 m NaOH (or KOH) solution was generally used for the alkaline treatment of adsorbent fibers prepared by RIGP or ATRP from PE trunk fibers.…”
Section: Characterization Of Pido Nfsmentioning
confidence: 86%
See 3 more Smart Citations
“…[3,[20][21][22][23][24][25] However, in this study, we found that 10 × 10 −3 m NaOH solution is enough to "active" the imide dioxime and/or amidoxime groups sufficiently. In most of the previous studies, 0.44 m NaOH (or KOH) solution was generally used for the alkaline treatment of adsorbent fibers prepared by RIGP or ATRP from PE trunk fibers.…”
Section: Characterization Of Pido Nfsmentioning
confidence: 86%
“…NH 2 OH·HCl (12 g) was completely dissolved into DMF (100 mL), NaOH (6.9 g) was added to the solution and mixed with vigorous magnetic stirring for 2 h. After that, PAN powder (10 g) was added to the solution, the mixture was stirred for another 30 min at Adv. [18,[20][21][22][23][24]32] room temperature, then transferred to an oil bath, and kept at 80 °C for 12 h with continuous mechanical stirring. 2018, 8, 1802607 Figure 5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, amidoxime binding chemistries for the targeted separation of uranium from seawater have been identified, but current substrates result in problematic low uptake capacities. 138,139 The block polymer platform lends itself well to such instances due to its structural characteristics and easily modified chemical properties. These features could, likewise, improve the separation performance of membranes lined with phosphate-chelating agents for the recovery of phosphorus from wastewater streams.…”
Section: Modifying the Pore Wall Chemistry For Advanced Solute Separamentioning
confidence: 99%